2016
DOI: 10.1590/00115258201691
|View full text |Cite
|
Sign up to set email alerts
|

Activismo y Prácticas Digitales en la Construcción de una Esfera LGTB en España

Abstract: E ste artículo analiza la forma en que la existencia de los colectivos de Lesbianas, Gays, Transexuales y Bisexuales (LGTB), sus prácti-cas, sus protestas y los medios digitales inciden en la protesta colectiva y en la construcción de una esfera LGTB en España. En particular, se centra en la forma en que los colectivos LGTB españoles utilizan los medios digitales. Si bien trata de entender también cómo otras plataformas digitales se ocupan de cuestiones LGTB y cómo la relación entre recursos digitales, accione… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 7 publications
0
3
0
6
Order By: Relevance
“…Beyond the different and sometimes less rigorous ways of naming the relationship between activism mediated by digital technologies and education, the literature review revealed a broad set of political practices which involve different levels of participation: critical and active media consumption, searching for and circulating information, coordination of actions, content production, hacker practices. Likewise, in the different texts, activism mediated by digital technologies (or this concept referred to with different terms) is associated with various forms of technological appropriation that have diverse practices and purposes: raising awareness, protesting or defending certain causes of interest, promoting social mobilization, creating new forms of citizen participation, generating local, national and global collaboration networks, and strengthening solidarity and a sense of community (Pearson et al, 2016;Linder et al, 2010;Khoury-Machool, 2007;Theocharis, 2012;Peña, Rodríguez, & Sáez 2016;Enguix, 2016;González-Lizarraga, Becerra-Traver, & Yanez-Díaz, 2016;Vivitsou & Viitanen, 2015;Weeks, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Beyond the different and sometimes less rigorous ways of naming the relationship between activism mediated by digital technologies and education, the literature review revealed a broad set of political practices which involve different levels of participation: critical and active media consumption, searching for and circulating information, coordination of actions, content production, hacker practices. Likewise, in the different texts, activism mediated by digital technologies (or this concept referred to with different terms) is associated with various forms of technological appropriation that have diverse practices and purposes: raising awareness, protesting or defending certain causes of interest, promoting social mobilization, creating new forms of citizen participation, generating local, national and global collaboration networks, and strengthening solidarity and a sense of community (Pearson et al, 2016;Linder et al, 2010;Khoury-Machool, 2007;Theocharis, 2012;Peña, Rodríguez, & Sáez 2016;Enguix, 2016;González-Lizarraga, Becerra-Traver, & Yanez-Díaz, 2016;Vivitsou & Viitanen, 2015;Weeks, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, in several texts, emphasis is on non-formal education, understood as the education which is enacted on extracurricular spaces such as social organizations, social movements or NGO (e.g. Weeks, 1999;Enguix, 2016;Share & Shayne, 2008).…”
Section: Activism Mediated By Digital Technologies and Education: Conmentioning
confidence: 99%
See 1 more Smart Citation
“…El ciberactivismo en Túnez, el Libano y Egipto en materia de derechos LGTBQ+ no han sido profusamente analizados. Es posible encontrar trabajos realizados sobre ciberactivismo LGBTIQ+ en otros contextos geográficos: en ámbito nacional (Enguix Grau, 2016), contexto latinoamericano (Herrera, 2009;Garay Cruz, 2018). Monográficos sobre grupos poblacionales específicos (Campbell-Foster, 2017), estudios sobre ciberactivismo LGBTIQ+ en Twitter (Rodríguez Delgado, 2018) y también sobre identidades concretas como la transgénero (O'Riordan, 2005).…”
Section: Ciberactivismo En El Mundo áRabeunclassified
“…En Occidente, la esfera LGBTIQ+ suele incluir, en tanto que configuración compleja y dinámica que trasciende el activismo, prácticas digitales, grupos sociales, secciones en agrupaciones políticas, espacios físicos, lugares y acciones colectivas (Enguix Grau, 2016). Por el contrario, esta realidad no se configura así en todo el globo.…”
Section: Ciberactivismo En El Mundo áRabeunclassified